2009
DOI: 10.1093/hmg/ddp087
|View full text |Cite
|
Sign up to set email alerts
|

Association of the thyroid stimulating hormone receptor gene (TSHR) with Graves' disease

Abstract: Graves' disease (GD) is a common autoimmune disease (AID) that shares many of its susceptibility loci with other AIDs. The thyroid stimulating hormone receptor (TSHR) represents the primary autoantigen in GD, in which autoantibodies bind to the receptor and mimic its ligand, thyroid stimulating hormone, causing the characteristic clinical phenotype. Although early studies investigating the TSHR and GD proved inconclusive, more recently we provided convincing evidence for association of the TSHR region with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
2
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 40 publications
6
122
2
7
Order By: Relevance
“…Our study for single SNPs had 80% power (α=0.05) to detect a significant difference between ing the chances of autoantibody production against the TSHR. It has been reported that rs179247 and rs12101255 increase the level of ST4 and ST5 expressions compared to full length TSHR, and may support the hypothesis for disease pathogenesis [13]. In summary, we can conclude that the SNPs in TSHR intron1 and 8 are significantly associated with pathogenesis of AITD.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our study for single SNPs had 80% power (α=0.05) to detect a significant difference between ing the chances of autoantibody production against the TSHR. It has been reported that rs179247 and rs12101255 increase the level of ST4 and ST5 expressions compared to full length TSHR, and may support the hypothesis for disease pathogenesis [13]. In summary, we can conclude that the SNPs in TSHR intron1 and 8 are significantly associated with pathogenesis of AITD.…”
Section: Discussionsupporting
confidence: 72%
“…The case-control study in Japanese cohorts found that several SNPs spaced 3-50kb apart spanning the TSHR gene in intron7 and 8 were associated with GD, especially rs2268475(P=0.0004), rs1990595 (P=0.0086) and rs3783938 (P=0.0099) [12]. More recently, a screening for 98 SNPs spanning about 800kb of TSHR gene in UK European ancestry found that 28 SNPs were associated with GD, in which the most relevant SNPs were rs179247 (P=8.9×10 -8 , OR=1.53) and rs12101255 (P=1.95×10 -7 , OR=1.55) [13]. They also selected several SNPs from intron7, but no association was observed.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In the smaller of the two studies, the WTCCC investigated 5500 individuals, which included 900 cases with GD, using a genome-wide set of 14 500 nonsynonymous coding single-nucleotide polymorphisms (nsSNPs). Although the strongest association signal was unsurprisingly identified in the human leukocyte antigen (HLA) region (P valueo10 À20 ), association was also confirmed at the previously reported thyroid stimulating hormone receptor gene (TSHR) 5 and Fc receptor-like 3 gene (FCRL3), 4,6 with a further nine novel regions showing some evidence of association with P valuep10 À4 . 4 The aim of this study was to try to replicate the association identified in the nine novel regions in an independent UK collection of GD subjects and controls.…”
Section: Introductionsupporting
confidence: 64%
“…The FCRL and TSHR regions were not examined as association with AITD had been previously reported. [4][5][6] A further tenth SNP, rs3748140, present within the protein phosphatase 1 regulatory inhibitor Subunit 3B gene (PPPIR38) also produced a point-wise significance level of Pp10 À4 but was excluded from further analysis as it was non-polymorphic in the replication study.…”
Section: Nssnp Genotypingmentioning
confidence: 99%